Tingkat Konsumsi Energi, Protein, Lemak, Karbohidrat Dan Kesukaan Makanan Jajanan Pada Remaja Obesitas (Studi di SMAN 3 Banjarbaru ) - magdalena, magdalena (Politeknik Kementerian Kesehatan Banjarmasin, 2024)
Abstract : Obesity in adolescents is caused by many factors including an imbalance in diet, often consuming fast food. Someone who has an unhealthy diet usually consumes more foods with high levels of fat or sugar. These ingredients can make teenagers experience weight gain. Objective: The aim of the study was to determine the level of consumption of energy, protein, fat, carbohydrates and preferences for snack foods in obese adolescents. Method. This type of research is descriptive observational, instrumentfood recall on energy, protein, fat, carbohydrate consumption level variables (Category consumption levels based on the Adequacy of Nutritional Adequacy Rate (RDA): more: > 100%, Good: > 90 - 100%, moderate: > 80 - 90%, less: 70 - 80 %, deficit: <70% and a list of favorite snacks.The population in this study were 32 students of SMAN 3 Banjarbaru.The sampling technique waspurposive sampling, independent variables: Results: The results of this study are:the age of the largest respondent is 16 years, namely (59.4%), the largest gender is female (93.7%). The highest level of calorie consumption is in the more and better category (25%), the highest level of protein consumption is in the moderate and less category (25%), the highest level of fat consumption is in the less category (31.25%) and the highest level of carbohydrate consumption is in the moderate category ( 28.125%). The most choices of snacks that are the favorite choices of teenagers are: fried potatoes, fried noodles, grilled chicken, soy sauce fried chicken, Kentucky chicken and brown bread, each 93%.